Interrelationships between Acoustic Emission and Cutting Force in Rock Cutting - Sifei Liu; Peng Shi; Zhijun Wan; Shuaifeng Lu; Jiakun Lv; Fanfei Meng (Geofluids)
Cutting force is the key signal to realize intelligent control of shearer and mastering the change process of cutting force is helpful to improve the adaptive cutting of shearer. In this paper, full scale rock cutting tests are used to carry out single pick cutting experiments on three kinds of coal, and the acoustic emission (AE) signals of coal and rock cutting are monitored in the whole process. The relationship between AE and cutting force is also discussed. The results show that the development of AE energy can represent the different stages of the cutting process, and the time fractal dimension of AE energy can reveal the change law of coal structure stability. In addition, the acoustic emission waveform at the peak cutting force of the same kind of coal has the same main frequency, power spectrum density (PSD) variation law, and the area under PSD curve; for different types of coal, the area under PSD curve at peak cutting force increases with the increase of USC. In the cutting process, the AE signal has obvious characteristics and internal evolution law in energy amplitude, fractal dimension, and PSD index. The change characteristics of AE energy can be used as the precursor information of the peak cutting force, and the coal failure at the peak cutting force has the identity. The above conclusions are of great significance for intelligent control of shearer and intelligent mining of coal mine.